Genetic diversity of Siberian bovine coronavirus isolates (Coronaviridae: Coronavirinae: Betacoronavirus-1: Bovine-Like coronaviruses) - Alexander G. Glotov; Aleksej V. Nefedchenko; Anton G. Yuzhakov; Svetlana V. Koteneva; Tatyana I. Glotova; Alina K. Komina; Nikita Yu. Krasnikov (Вопросы вирусологии, 2023)
Introduction. Bovine coronaviruses (BCoVs) are causative agents of diarrhea, respiratory diseases in calves and winter cow dysentery. The study of genetic diversity of these viruses is topical issue.